2020
DOI: 10.1093/jncics/pkaa082
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breast Cancer Adjuvant Chemotherapy Regimens on Expression of the Aging Biomarker, p16INK4a

Abstract: Background While chemotherapy saves lives, increasing evidence shows that chemotherapy accelerates aging. We previously demonstrated that mRNA expression of p16INK4a, a biomarker of senescence and molecular aging, increased early and dramatically after beginning adjuvant anthracycline-based regimens in early-stage breast cancer patients. Here, we determined if changes in p16INK4a expression vary by chemotherapy regimen among early-stage breast cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
1
22
2
Order By: Relevance
“…Surprisingly, we found that patients with the greatest risk were chronologically older but molecularly younger (lower p16 expression). Although our findings of higher CIPN risk for those with age-inappropriately low p16 (low p16Age Gap) initially seemed counterintuitive, this paradoxical result can be understood in the context of data demonstrating that patients with lower baseline p16 expression are more likely to have a larger chemotherapy-induced increase in p16 49 (Figure 3A). And larger chemotherapy-induced change in p16 expression (pre-treatment to post-treatment) is associated with higher CIPN risk (Figure 3B).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Surprisingly, we found that patients with the greatest risk were chronologically older but molecularly younger (lower p16 expression). Although our findings of higher CIPN risk for those with age-inappropriately low p16 (low p16Age Gap) initially seemed counterintuitive, this paradoxical result can be understood in the context of data demonstrating that patients with lower baseline p16 expression are more likely to have a larger chemotherapy-induced increase in p16 49 (Figure 3A). And larger chemotherapy-induced change in p16 expression (pre-treatment to post-treatment) is associated with higher CIPN risk (Figure 3B).…”
Section: Discussioncontrasting
confidence: 53%
“…Finally, we asked why patients with lower baseline p16 expression may be at higher risk of CIPN. We previously showed that p16 expression prior to chemotherapy is inversely correlated with the magnitude of chemotherapy-induced p16 increase 49 (also Figure 3A). Patients who experienced a post-chemotherapy increase in p16 were twice as likely to develop CIPN (37.5% vs 18.3%, p=0.02) as patients whose p16 did not change (Figure 3B).…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…In stage 0-IIIa breast cancer patients analyzed a median of 6.2 months after their last round of chemotherapy, anthracycline-based regimens significantly upregulated p16 INK4 comparably to 23-26 years chronologic aging. In contrast, non-anthracycline regimens nonsignificantly increased p16 INK4 levels by a magnitude equivalent to 9-11 years of chronologic aging (155).…”
Section: Telomere Attritionmentioning
confidence: 78%
“…The above-mentioned mechanism may explain the accumulation of senescent cells observed in cancer patients undergoing radiotherapy/chemotherapy regimen and associated with high risk of premature age-related cardiovascular complications [49••]. Clinical studies reported that patients receiving chemotherapy treatment have accumulation of p16 INK4a -positive cells in different tissues, including the heart [50][51][52][53], which is detected within 1 year from treatment interruption [52][53][54].…”
Section: Autophagy At the Crossroad Of Cell Survival And Senescence In Doxo-mediated Cardiotoxicitymentioning
confidence: 99%